Dynamics of SARS-CoV-2 lineages in children and adults in 2021 and 2022. - Hiie Soeorg; Aare Abroi; Taavi Päll; Liidia Dotsenko; Erik Jaaniso; Katrin Kaarna; Andrio Lahesaare; Paul Naaber; Heiki Niglas; Ott Eric Oopkaup; Hedi Peterson; Tuuli Reisberg; et al. (PLoS ONE)
Purpose We aimed to describe SARS-CoV-2 lineages and diversity in children and adults in Estonia and similarity to travel-related cases and neighbouring countries. Methods SARS-CoV-2 sequences in 2021-2022 from a nationwide study were included. The proportion of predominant lineages in Estonian regions and among travel-related cases was described by multinomial logistic regression. Simpson's indices of diversity were compared using linear regression. Dynamics of Bray-Curtis dissimilarity was described by applying fuzzy clustering to non-metrical dimensional scaling results. Results A total of 2,630 sequences from children (<15 years) and 23,031 from adults (≥15 years) were included. The increase in the proportion of Alpha/Delta/Omicron BA.1/BA.2 lineages was delayed in smaller regions (by 3.5-27.5 days). The proportion of Alpha/Delta/Omicron BA.1 increased earlier among travel-related (n = 4,654) than non-travel-related cases (10.5 days). Diversity was lower in non-travel-related than travel-related cases until Delta period by 0.066. Dynamics of lineages and diversity were similar in adults and children. Similarity of lineages was delayed compared to Finland during Alpha/Omicron BA.1/BA.2 periods and different from all neighbouring countries during Delta period. Conclusion SARS-CoV-2 lineages in children and adults were similar. Differences between regions and travel-related cases and varying similarity to neighbouring countries suggest the importance of mobility in the spread.